PREVALENCE, ETIOLOGY AND PATHOGENESIS OF CHRONIC RENAL FAILURE - Murtazoev, B.S. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
Chronic glomerulonephritis, diabetic nephropathy, arterial hypertension are the main reasons for the increase in the number of patients with chronic renal failure. The main task facing nephrologists, urologists, endocrinologists, cardiologists and therapists is to postpone the onset of the terminal stage of chronic renal failure with the need for hemodialysis among patients with kidney pathology. the continuing high mortality rate among patients with the terminal phase of chronic renal failure, which, according to a number of authors, ranges from 52.1% to 67.9%. From these data, it follows that the issues of prevention of renal failure are important and relevant. This review article presents modern information on the prevalence, etiology and pathogenesis of chronic renal failure.